Effect of Oxygen Plasma on Tin Oxide Nanorods Prepared by GLAD Technique - Oros*, Chaiyan (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this work, the effect of oxygen plasma with varing plasma power from 100 W to 300 W on tin oxide (SnO2) nanorods prepared by glancing angle deposition (GLAD) technique was studied. The crystal structures were characterized by X-ray diffraction (XRD) technique and the morphology was characterized by field-emission scanning electron microscopy (FE-SEM) technique. Atomic-force microscopy (AFM) revealed that the as-deposited and oxygen plasma-treated tin oxide nanorod structures had orthorhombic phase of SnO2. The degree of crystallinity tended to improve as the plasma power increasd from 100 W to 300 W In addition, the surface roughness of tin oxide nanorods increased with oxygen plasma power increasing. However, the thickness decreased with oxygen plasma power increasing. Keywords: Oxygen plasma, tin oxide nanorods, GLAD technique *Corresponding author: E-mail: Chaiyan.Oro@rmutr.ac.th